IMPLEMENTATION OF THE RESTITUTION TRIANGLE METHOD IN REDUCING CHILD DELINQUENCY AT SDN 4 WONOSARI MUSI RAWAS SOUTH SUMATERA - Rozikin; Lud Waluyo; Iis Siti Aisyah (RADJA PUBLIKA, 2025)
This study aims to implement the Restitution Triangle method as an effective strategy in reducing juvenile delinquency in the school environment, especially at SDN 4 Wonosari, Musi Rawas, South Sumatra. The Restitution Triangle method is a restorative approach that involves collaboration between the school, parents, and children as the main actors in the process of recovery and prevention of delinquency. This study uses a descriptive quantitative approach with data collection techniques through observation, interviews, and questionnaires to students, teachers, and parents during the study period. In its application, this method focuses on open dialogue, moral responsibility, and a recovery process that involves all related parties to build children's awareness of the impact of their actions and repair damaged social relationships. The results of the study indicate that the implementation of the Restitution Triangle Method is significantly able to reduce the level of student delinquency, improve communication between schools and parents, and form more positive and responsible behavior among children. This implementation also shows an increase in students' moral awareness and empathy towards their families and the surrounding community. Based on these findings, it is suggested that this method can be routinely integrated into character education programs and child behavior management in elementary schools to create a healthy, safe, and understanding learning environment. This study contributes to the development of discipline strategies based on a restorative approach and is able to reduce child delinquency effectively.